Corporate Governance in Asia: A Comparative Study - Barghouthi, Orobah Ali (International Journal of Shari'ah and Corporate Governance Research, 2018)
The World Bank has done 10 Report on the Observance of Standards and Codes (ROSC) studies of corporate governance for Asian countries. The paper it used was based on the categories used in an Organisation for Economic Co-operation and Development publication (OECD, 2004).